2012
DOI: 10.1016/j.neuroimage.2012.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Validating atlas-guided DOT: A comparison of diffuse optical tomography informed by atlas and subject-specific anatomies

Abstract: We describe the validation of an anatomical brain atlas approach to the analysis of diffuse optical tomography (DOT). Using MRI data from 32 subjects, we compare the diffuse optical images of simulated cortical activation reconstructed using a registered atlas with those obtained using a subject’s true anatomy. The error in localization of the simulated cortical activations when using a registered atlas is due to a combination of imperfect registration, anatomical differences between atlas and subject anatomie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 30 publications
1
96
3
Order By: Relevance
“…The details of the MRI scan preprocessing steps and of the segmentation procedure have been previously described. 40 Contrary to a previous study where we reported the performance of the FDMD approach at one specific location on the head, 28 in the present work, we show a systematic characterization of the TD-NIRS fitting methods at various locations over the whole head. We defined three two-dimensional (2-D) arrays of optodes with 1 cm spacing, to be placed over the frontal (6 × 20 optodes), left parietotemporal (12 × 14), and occipital (8 × 20) regions.…”
Section: Simulated Datacontrasting
confidence: 91%
See 3 more Smart Citations
“…The details of the MRI scan preprocessing steps and of the segmentation procedure have been previously described. 40 Contrary to a previous study where we reported the performance of the FDMD approach at one specific location on the head, 28 in the present work, we show a systematic characterization of the TD-NIRS fitting methods at various locations over the whole head. We defined three two-dimensional (2-D) arrays of optodes with 1 cm spacing, to be placed over the frontal (6 × 20 optodes), left parietotemporal (12 × 14), and occipital (8 × 20) regions.…”
Section: Simulated Datacontrasting
confidence: 91%
“…Three subjects were selected from a library of 32 head volumes, previously used by Cooper et al to validate the use of atlas-based image reconstructions of functional data. 40 We chose three subjects which resulted in poor, average, and good performance in the functional NIRS study. The head volumes were segmented using FreeSurfer (http://surfer.nmr.mgh.harvard.edu) 41,42 into four tissue types: extracerebral tissue (skin and skull), cerebrospinal fluid (CSF), gray matter, and white matter.…”
Section: Simulated Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Custo et al 1 initially introduced the concept of atlas-DOT, after which it was further developed with high-density optodes and successfully validated using computational simulations and functional magnetic resonance imaging (fMRI) performed on human subjects. [2][3][4] Atlas-DOT utilized a finite element technique with either subject-specific models 3,4 or a standard magnetic resonance imaging (MRI) brain template (such as ICBM 256) in the forward calculation. 5,6 A significant improvement of accuracy in image reconstruction and source localization has been achieved with atlas-DOT.…”
Section: Introductionmentioning
confidence: 99%